Monetization of Tiktok Affiliate Marketing on Customer Engagement of Skin Care Products: A Halal Social Media Perspective - Rose Rachmadi, Kartika; Sugiarti Ramadhan, Tri (Dinasti Publisher, 2024)
Halal industry is not only in products such as food, drinks or products that can be consumed directly, but also in the use of social media. The content available on social media, in this case TikTok, is not only content in entertainment packaging but also marketing a product. Skin care products are no exception. There is content that has been created by affiliates on TikTok to attract consumers to make purchases. This study provides findings on how halal social media in moderating the relationship between tiktok affiliates and the number of consumers interested in skin care products. The implication is that, for business actors, investing in social media, especially to make their products in accordance with Islamic sharia, will provide benefits, especially so that Muslim consumers can choose or buy these products. As for the research conducted, it was found that In the model, the results of the analysis show findings that the determinants of consumer intention to purchase halal cosmetic products are significantly influenced through all variables, namely Tiktok Affiliate Marketing, Custoner Engagement, and Halal Social Media where all the hypotheses proposed are proven to fulfill the initial hypothesis proposed.